Faktor Kualitatif Service-Profit Chain dalam Bisnis Franchise Restoran - Ireene*, Ireene (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Understanding the factors that can influence business success may contribute to improving the food and beverages business concept, which has a large market potential in Indonesia. The factors that are of concern in this research are qualitative factors, based upon the idea in the service-profit chain theory. Research problem of this article is "what are the qualitative factors that may influence restaurant franchise business? And how do these factors influence the performance of the restaurant franchise business? The discussion of this research elaborates on these qualitative factors, which include external and internal dimensions, namely the business itself and its employees, namely how they provide services, manage their assets, and design their products, as the so-called the 'internal dimension', while factors related to customer psychology are the 'external dimension'. Successful restaurant franchises provide examples on how considering these factors in running their business, may contribute to their success. The service-profit chain theory may be used alongside supporting concepts, to develop the business concept further.